Prevalence of acne vulgaris, its contributing factors, and treatment satisfaction among the saudi population in Riyadh, Saudi Arabia: A cross-sectional study - Tammam M Alanazi; Waleed Alajroush; Raghad M Alharthi; Mohammed Z Alshalhoub; Mona A Alshehri (Wolters Kluwer Medknow Publications, 2020)
Introduction: Acne vulgaris is one of the most common inflammatory disorders worldwide and mainly affects young people. The frequency of acne and how it is treated in Saudi Arabia is not well characterized. Purpose: The aim of the study was to determine the prevalence of acne vulgaris among the Saudi population in Riyadh, Saudi Arabia. Methods: This was a cross-sectional survey study that was carried out in Riyadh, Saudi Arabia, in the period from March to July 2019. The questionnaire was filled by a convenience sample of 346 Saudi participants aged 15-30 years. The survey questions were related to acne prevalence, associated factors, treatment practices, and depression. Results: Seventy-eight percent of the participants reported having acne. Females were more commonly affected (86.1%) than males (69.9%, P < 0.001). Only 31.5% of the individuals who had acne consulted a dermatologist in the past 12 months. The most frequently prescribed medication was isotretinoin (19.2%), and 71.4% were happy with the results of using it compared to only 38.2% who used topical antibiotics (P= 0.012). Males reported a less depression (21.5%) compared to females (46.3%, P < 0.001). Conclusions: Acne vulgaris has a high prevalence in Saudi Arabia, but only one-third are getting treated by health-care providers. Efforts should be made to increase awareness about acne vulgaris and its treatment.